HUBUNGAN TINGKAT KECUKUPAN VITAMIN A, C, E DAN SENG SEBAGAI ANTIOKSIDAN DENGAN TEKANAN DARAH SISTOLIK DAN DIASTOLIK PADA IBU HAMIL DI PUSKESMAS BANGETAYU KOTA SEMARANG - Hilaria Dita Regi; Martha Irene Kartasurya; Suyatno Suyatno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Hypertension may cause pre-eclampsia that may lead to mortality. Puskesmas Bangetayu has the highest case of pre-eclampsia in Semarang, which is 14 cases of severe preeclampsia in 2014. The purpose of this study was to discover the association between vitamin A, C, E, and Zinc adequacy ratio as antioxidant and systolic-diastolic blood pressure of pregnant women. This observational analytic study used quantitative method with cross-sectional study design. Population of this study is pregnant women in the operational area of Puskesmas Bangetayu in July-August 2017. Eighty-five subjects were chosen using purposive sampling technique. Structured interview, Food Frequency Questionnaire, physical activity recalls, and blood pressure measurement were used to collect the data. The data was processed with Rank Spearman and Chi Square. The result showed that most of the subjects had normal systolic-diastolic blood pressure, adequate ratio of vitamin C, and inadequate ratio of vitamin A, E and zinc. About 67% of subjects had energy deficiency, 50.6% had protein deficiency, and the mean of fat intake was 12.7%. This study demonstrates that there are associations between vitamin C adequacy ratio and systolic (p-value=0.009) and diastolic (p-value=0.017) blood pressure. There is no association between vitamin A, E, and zinc adequacy ratio with blood pressure. Puskesmas is suggested to take care of maternal antioxidant requirement and provide education concerning antioxidant-rich foods.